Crosstalk between mitochondrial homeostasis and AMPK pathway mediate the receptor-mediated cardioprotective effects of estradiol in ovariectomized female rats - Gowayed, Mennatallah A.; Zakaraya, Zainab Zaki; Abu-Samra, Nehal; Elhamammy, Reem H.; Abdel Moneim, Lobna M.; Hafez, Hala A.; Moneam, Ihab A.; Oriquat, Ghaleb A.; Kamel, Maher A. (PLOS ONE, 2024)
Estrogen (E2) deficiency is a risk factor for cardiovascular disease (CVD), however, the exact mechanism for the E2 protective effect on CVD remains unclear. This study aimed to investigate the estrogen receptor (ER) and non-receptor mediated effects of E2 treatment on the cardiac expression of adenosine monophosphate-dependent protein kinase (AMPK), autophagic, mitophagy and mitochondrial homeostasis-regulating genes in ovariectomized (OVX) rats. Female rats were divided into two main groups; sham and bilaterally OVX rats, then each group was subdivided into four subgroups according to treatment; untreated, subcutaneously treated with E2 (30 μg/kg), or Fulvestrant (F) (5 mg/Kg), or a combination of both drugs for 28 days. The OVX rats or F-treated sham rats showed dyslipidemia, and marked disturbances in parameters of AMPK signaling, autophagy, mitophagy, mitochondrial fission, fusion and biogenesis. E2 administration to OVX or F-treated sham rats has corrected the disturbed lipid and cardiac profiles, increased AMPK, and restored the balance of cardiac autophagy, mitophagy, and mitochondrial dynamics and homeostasis. Most of these effects in OVX rats were blocked by the ER antagonist (F). Estrogen treatment has cardioprotective effects in OVX females through modulating cardiac mitochondrial homeostasis, mitophagy and autophagy and restoring the AMPK signaling pathway. As witnessed by Fulvestrant, these effects suggest the main role of ER-mediated signaling in regulating mitophagy and plasma and cardiac lipids along with the existence of a post-translational control mechanism or the involvement of estrogenic non-receptor pathway controlling the postmenopausal cardiac mitochondrial energy production machinery that needs further investigation.